Nano MOFs loaded bio-based fiber photo-Fenton catalytic material as well as preparation method and application thereof

By preparing Fe0.2-MOFs/CF composite materials on cotton fibers and utilizing the synergistic effect of 4-carboxyphenylporphyrin TCPP and Fe, the problems of insufficient recyclability and free radical yield of Fenton-like catalysts were solved, achieving efficient degradation of tetracycline TC and other organic pollutants. This method is characterized by being green, environmentally friendly, and easy to recycle.

CN120790237AActive Publication Date: 2025-10-17NANJING DEPURATE ENVIRONMENTAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511309006.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-10-17
Estimated Expiration
2045-09-15

AI Technical Summary

Technical Problem

Existing Fenton-like catalysts have problems such as difficulty in recycling and slow metal valence state cycling leading to insufficient free radical yield when degrading organic pollutants. Furthermore, photo-Fenton technology lacks environmentally friendly and efficient catalysts in practical applications.

Method used

Using 4-carboxyphenylporphyrin TCPP as an organic ligand and Fe as a central metal, nano-MOFs were grown in situ on cotton fibers via a hydrothermal method to prepare Fe0.2-MOFs/CF composite materials. The binding ability of nano-MOFs to bio-based fibers was enhanced by plasma cleaning and alkalization treatment, which promoted the separation of photogenerated electron-hole pairs and Fenton synergistic effect.

Benefits of technology

It achieves efficient, green, and environmentally friendly degradation of organic pollutants, especially tetracycline (TC) with a removal rate of 99.13%. Furthermore, the catalyst is easy to recover, has a fast degradation rate, and strong anti-interference ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120790237A_ABST
    Figure CN120790237A_ABST
Patent Text Reader

Abstract

The invention provides a nano-MOFs loaded bio-based fiber photo-Fenton catalytic material as well as a preparation method and application thereof.The nano-Fe-MOFs are prepared by taking a green and environment-friendly photosensitive material 4-carboxyl phenyl porphyrin TCPP as an organic ligand and Fe < 2 + > as a central metal, and the nano-Fe-MOFs are loaded to the surface of bio-based cotton fiber for photo-Fenton degradation of organic pollutants. The enhanced combination of the nano Fe-MOFs and the bio-based cotton fiber mainly comprises the steps of plasma cleaning, alkalization treatment and carboxymethyl treatment of the fiber, and compared with a traditional powder catalytic material, the composite material Fe-MOFs / CF of a three-dimensional structure is convenient to recycle after being used, and the actual use performance of the material is greatly improved. The method has the advantages of being green, environmentally friendly, high in degradation rate, high in removal rate, convenient to recycle and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of bio-based environmentally friendly materials and nano metal organic framework materials, and relates to the fields of nano material and bio-based carrier combination technology, photocatalysis technology, Fenton-like degradation and organic matter removal. Specifically, it relates to a nano MOFs loaded bio-based fiber photo-Fenton catalytic material, a preparation method and an application thereof. BACKGROUND

[0002] With the development of the degradation of persistent organic pollutants in wastewater, antibiotics have been regarded as emerging pollutants. Their persistent impact on the entire ecosystem has directly led to irreversible damage worldwide. At present, the methods for removing antibiotics and other organic pollutants mainly include ion exchange, microbial treatment, membrane filtration, adsorption and Fenton advanced oxidation degradation, among which the Fenton-like advanced oxidation method is considered to be one of the most promising methods in the removal of organic pollutants due to its strong oxidation degradation capacity, no pollution, environmental protection and simple operation. The Fenton-like reaction is an advanced oxidation process for degrading organic pollutants by using transition metals (such as iron, copper, manganese, etc.) or their compounds to catalyze hydrogen peroxide to generate highly active free radicals (such as ·OH). Common Fenton-like catalysts include iron oxides, copper oxides, single-atom catalysts, metal organic frameworks MOFs, etc. Among various Fenton-like catalysts, MOFs exhibit great potential in the field of catalytic degradation due to their active center metals, large specific surface area and rich pore structure. However, there are still some deficiencies in the Fenton-like reaction process. For example, the powder-like Fenton-like catalysts are not easy to recover, and the slow metal valence state cycle in the Fenton-like catalysts leads to insufficient free radical yield. In order to improve the free radical conversion efficiency, some studies use photo-Fenton technology to improve the degradation efficiency. The photo-Fenton technology significantly improves the generation efficiency of free radicals by introducing ultraviolet light or visible light on the basis of Fenton, thereby enhancing the degradation capacity of organic pollutants. In the reaction process, the photo-Fenton catalyst plays an important role, which not only can activate hydrogen peroxide, but also can be excited by light to generate photo-generated electrons to promote the metal valence cycle. Therefore, it is necessary to explore some environmentally friendly, high-efficiency and easy-to-recover photo-Fenton catalysts. SUMMARY

[0003] In view of the above technical problems, the present application provides a nano MOFs loaded bio-based fiber photo-Fenton catalytic material, a preparation method and an application thereof. In order to enhance the binding ability of nano MOFs and bio-based cotton fibers, a series of pretreatments such as plasma cleaning, alkalization treatment and carboxymethylation are performed on the cotton fibers CF. A nano MOFs is in-situ grown on the surface of the cotton fibers CF by using a photosensitive material 4-carboxyphenyl porphyrin TCPP as an organic ligand and Fe as a central metal through a hydrothermal method, and a Fe 0.2MOFs / CF composite materials. 4-carboxyphenyl porphyrin TCPP has good visible light capturing ability as a green organic ligand, especially it can be implanted in the center of a rigid skeleton as a single atom, so 4-carboxyphenyl porphyrin TCPP is mainly used as a component of various MOFs with photosensitive properties. The light-induced e − Can be transferred to Fe3O(COO)6, causing Fe (III) to accelerate the reduction of Fe (II) to further promote the generation of free radicals. With photosensitizer 4-carboxyphenyl porphyrin TCPP as an organic ligand and Fe ion with Fenton activity as a central metal, Fe-MOFs are synthesized by hydrothermal synthesis, and are loaded on cotton fibers to improve their dispersibility and practicability. At the same time, this combination promotes the separation of photo-induced electron-hole pairs, improves the redox ability of Fe(II) / Fe (III) in MOFs, and greatly improves the degradation efficiency through the synergistic effect of photocatalysis and Fenton.

[0004] The catalyst activates H2O2 to produce free radicals under light conditions, and the generated free radicals attack tetracycline TC and other organic pollutants and decompose them into small molecules CO2 and H2O. The degradation system of the application has the advantages of green, environmental protection, fast degradation rate, high removal rate, strong anti-interference ability, easy recovery, etc., and is successfully used for tetracycline TC and other organic pollutants degradation.

[0005] The application achieves the above technical purposes through the following technical means.

[0006] A preparation method of a nano MOFs loaded bio-based fiber light Fenton catalytic material, characterized in that it comprises the following steps: Step S1, pretreatment of bio-based cotton fiber CF: The cleaned cotton fiber CF is subjected to plasma cleaning for 60S, then subjected to alkalization treatment for activating cellulose in the cotton fiber CF, and finally subjected to carboxymethylation. This series of measures are conducive to the loading of metal organic framework MOFs; Step S2, nano MOFs bio-based fiber composite material Fe X Preparation of MOFs / CF: FeCl2•6H2O is dissolved in an organic solvent, then the pretreated cotton fiber CF in step S1 is immersed in the organic solvent for 8 h; then benzoic acid and 4-carboxyphenyl porphyrin TCPP are dissolved therein, and the ratio of benzoic acid: 4-carboxyphenyl porphyrin TCPP: FeCl2•6H2O is 30:1:5; hydrothermal reaction is carried out at 90 DEG C for 5 h to obtain Fe X MOFs / CF; then the prepared Fe X-MOFs / CF was first dried and then washed with ethanol to remove the undissolved ligands to obtain the final nano-MOFs bio-based fiber composite material Fe X -MOFs / CF;Fe X -In MOFs / CF, X represents the doping amount of FeCl2 • 6H2O; In this step, the ratio of benzoic acid: 4-carboxyphenylporphyrin TCPP: FeCl2 • 6H2O = 30:1:5 was kept unchanged, and the volume of the organic solvent was not changed. The loading rate of MOFs on cotton fiber CF was changed by changing the amount of FeCl2 • 6H2O.

[0007] Preferably, the alkalization treatment in step S1 is to swell the cotton fiber CF and activate the cellulose to facilitate better carboxymethylation. The alkali is a 20% to 30% by mass NaOH solution, 50 ml of NaOH solution corresponds to 0.5 g to 1.0 g of cotton fiber CF, and stirring is performed at room temperature of 25 to 30°C for 1 to 3 hours.

[0008] In the above scheme, the carboxymethylation in step S1 is intended to enhance the bonding between MOFs and cotton fiber CF. 50 ml of a 20% to 30% chloroacetic acid solution (mass ratio) corresponds to 0.5 g to 1.0 g of cotton fiber CF, and the reaction is carried out at 50°C to 70°C for 2 to 4 hours.

[0009] Preferably, the organic solvent in step S2 is any one of N,N-dimethylformamide and ethanol.

[0010] Preferably, in step S3, X is 0.05 to 0.25. In step S3, the ratio of benzoic acid: 4-carboxyphenylporphyrin TCPP: FeCl2 • 6H2O = 30:1:5 is kept unchanged, and the volume of the organic solvent is kept unchanged. The amount of FeCl2 • 6H2O is changed to achieve the change of the loading rate of MOFs. X The contents of benzoic acid, 4-carboxyphenylporphyrin TCPP, and FeCl2 •6H2O in -MOFs / CF were 0.3 g, 0.01 g, and 0.05 g; 0.6 g, 0.02 g, and 0.10 g; 0.9 g, 0.03 g, and 0.15 g; 1.2 g, 0.04 g, and 0.20 g; and 1.5 g, 0.05 g, and 0.25 g, respectively; the content of pretreated cotton fiber CF was fixed at 0.5 g.

[0011] Preferably, the step S3 Fe X-MOFs / CF, wherein X is optimal at 0.2, i.e. benzoic acid, 4-carboxyphenyl porphyrin TCPP, FeCl2·6H2O, 1.2 g, 0.04 g, 0.20 g, respectively, and the nano MOFs bio-based fiber composite material is Fe 0.2 -MOFs / CF.

[0012] A MOFs bio-based fiber composite material Fe 0.2 -MOFs / CF in the application of degrading and removing tetracycline TC and other organic pollutants. The other organic pollutants include methyl orange MO, methyl blue MB, norfloxacin NFX, enrofloxacin ENR, oxytetracycline OTC.

[0013] In the above scheme, the nano MOFs bio-based fiber composite material Fe 0.2 -MOFs / CF in the application of catalyzing hydrogen peroxide H2O2 to generate free radicals to oxidize and degrade tetracycline TC and other organic pollutants under light conditions, including the following steps: The nano MOFs bio-based fiber composite material Fe 0.2 -MOFs / CF is added to the water containing tetracycline TC and other organic pollutants to be treated, hydrogen peroxide H2O2 is added under xenon lamp light, the pH is adjusted, and the nano MOFs bio-based fiber composite material Fe 0.2 -MOFs / CF catalyzes H2O2 to generate free radicals to degrade and remove TC and other organic pollutants.

[0014] Further, the nano MOFs bio-based fiber composite material Fe 0.2 The dosage of MOFs / CF is 0.05 g·L –1 ~0.25 g·L –1 ; the use amount of hydrogen peroxide H2O2 is 5 mM ~ 40 mM, the pH is adjusted to 2 ~ 10; the organic pollutants are 10 mg·L –1 ~100 mg·L –1 ; and the xenon lamp light intensity is 100 mW / cm².

[0015] Further, the nano MOFs bio-based fiber composite material Fe 0.2 The dosage of MOFs / CF is 0.20 g·L –1 .

[0016] Further, the use amount of hydrogen peroxide H2O2 is 30 mM.

[0017] Further, the pH is 6.

[0018] Further, the organic pollutants 50 mg·L –1 .

[0019] Compared with the prior art, the application has the beneficial effects of: (1) The application uses 4-carboxyphenyl porphyrin TCPP as an organic ligand and ferrous ions as a central metal to prepare a new type of nano MOFs and load them on a bio-based fiber for efficient degradation of organic pollutants by photo-Fenton.

[0020] (2) The application provides a bio-based fiber surface treatment method to enhance the loading effect of nano MOFs, i.e., plasma cleaning, alkalization treatment, and carboxymethylation treatment. The three procedures can greatly enhance the binding capacity of nano MOFs and fibers and improve the usability and recyclability of the material.

[0021] (3) The Fe 0.2 -MOFs / CF prepared by the application has good stability and high removal efficiency for tetracycline TC and other organic pollutants under light catalysis of H2O2, and especially for tetracycline TC, which can achieve a removal rate of 99.13% after 60 min of degradation. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 is a preparation process schematic diagram; Figure 2 is a mechanism diagram of photo-Fenton degradation of TC; Figure 3 is a scanning electron microscope image of the material, Figure 3 (a) in the figure is a scanning electron microscope image of fresh cotton fiber CF, Figure 3 (b) in the figure is an electron microscope image of the cotton fiber after alkaline treatment and carboxymethylation treatment, Figure 3 (c) in the figure is an electron microscope image of the Fe 0.2 -MOFs / CF composite material, Figure 3 (d) in the figure is a local enlarged view of the Fe 0.2 -MOFs / CF composite material; Figure 4 is a characterization spectrum of the material, Figure 4 (a) in the figure is an XRD spectrum of Fe 0.2 -MOFs, CF, Fe 0.2 -MOFs / CF, Figure 4 (b) in the figure is an XPS spectrum of Fe 0.2 -MOFs, Fe 0.2 -MOFs / CF; Figure 5 is a composite material with different Fe doping ratios (Fe XThe removal rate of tetracycline TC by the MOFs / CF system; Figure 6 The influence of different conditions on the removal rate of tetracycline TC, Figure 6 The influence of different catalysts on the removal rate of tetracycline TC, Figure 6 The influence of different catalysts on the removal rate of tetracycline TC, Figure 6 The influence of different catalysts on the removal rate of tetracycline TC, Figure 6 The removal effect of the system on different concentrations of tetracycline TC; Figure 7 The removal effect of the system on different concentrations of tetracycline TC; Figure 7 The removal effect of the system on different concentrations of tetracycline TC; Figure 7 The removal effect of the system on different concentrations of tetracycline TC; Figure 8 The removal effect of the system on different concentrations of tetracycline TC; DETAILED DESCRIPTION

[0023] The examples described below by referring to the accompanying drawings are exemplary and are intended to serve for explaining the present application and cannot be understood as a limitation of the present application.

[0024] Example 1: A preparation method of a nano MOFs loaded bio-based fiber photo-Fenton catalytic material, comprising the following steps: MOFs bio-based fiber composite material Fe 0.2 Preparation steps of MOFs / CF: Step S1, pretreatment of cotton fiber CF: The cotton fiber CF is cleaned alternately with deionized water and ethanol, and after drying, plasma cleaning is used for 60 s to activate the oxygen-containing functional groups on the surface of the cotton fiber. Subsequently, alkalization treatment is carried out for the activation of cellulose in the cotton fiber CF, and 0.5 g of cotton fiber CF is soaked in 50 ml of NaOH solution with a mass ratio of 20%, and stirred at room temperature of 25℃ for 2h. Finally, carboxymethylation is carried out on the cotton fiber CF, and 0.5 g of cotton fiber CF is soaked in 50 ml of chloroacetic acid solution with a mass fraction of 20%, and reacted at 70℃ for 2h. As shown in Figure 3 (a), the surface of the fresh cotton fiber CF is very smooth. After plasma, alkalization treatment, and carboxymethylation treatment, the surface of the cotton fiber CF presents a spiral microfibril structure, which can well load the nano MOFs, and the structure is shown in Figure 3 (b).

[0025] Step S2, preparation of nano MOFs bio-based fiber composite material Fe XPreparation of MOFs / CF: Fe X Preparation of MOFs / CF is specifically to dissolve 0.05 g-0.25 g of FeCl2•6H2O in 40 ml of ethanol solution, then immerse the pretreated cotton fiber CF therein for 8 h. Then, 0.3 g-1.5 g of benzoic acid and 0.01 g-0.05 g of 4-carboxyphenyl porphyrin TCPP are dissolved therein, and the ratio of benzoic acid:4-carboxyphenyl porphyrin TCPP:FeCl2•6H2O is 30:1:5; hydrothermal reaction is carried out at 90°C for 5 h to prepare Fe X -MOFs / CF. Then, the prepared Fe X -MOFs / CF is dried and then washed to obtain the final nano-MOFs bio-based fiber composite Fe X -MOFs / CF.

[0026] Fe X In the preparation of MOFs / CF, the ratio of benzoic acid:4-carboxyphenyl porphyrin TCPP:FeCl2•6H2O is kept unchanged at 30:1:5, the amount of cotton fiber CF is fixed at 0.5 g, and the volume of organic solvent (40 ml) is kept unchanged, and the amount of FeCl2•6H2O is changed to realize the change of the loading rate of MOFs. Fe X In the MOFs / CF, the amounts of benzoic acid, 4-carboxyphenyl porphyrin TCPP and FeCl2•6H2O are respectively 0.3 g, 0.01 g and 0.05 g; 0.6 g, 0.02 g and 0.10 g; 0.9 g, 0.03 g and 0.15 g; 1.2 g, 0.04 g and 0.20 g; and 1.5 g, 0.05 g and 0.25 g. X represents the doping amount of FeCl2•6H2O, which is respectively 0.05, 0.10, 0.15, 0.20 and 0.25, i.e., Fe 0.05 -MOFs / CF, Fe 0.10 -MOFs / CF, Fe 0.15 -MOFs / CF, Fe 0.20 -MOFs / CF, Fe 0.25 -MOFs / CF, Fe 0.20 The scanning electron microscope image of the MOFs / CF is as shown in Figure 3 (c) and Figure 3 (d).

[0027] Example 2: The Fe X -MOFs / CF composite prepared in the application is used to catalyze hydrogen peroxide H2O2 to generate free radicals under light conditions for degrading tetracycline TC, and the specific steps include: (1) Preparation of tetracycline TC mother liquor: Take 100 mg of tetracycline TC into a 1L beaker, add 800 mL of deionized water, and ultrasonically dissolve it, then transfer it to a 1L volumetric flask and dilute to volume. Prepare a 100 mg·L –1 tetracycline TC mother liquor.

[0028] (2) Drawing of tetracycline TC solution standard curve: Dilute the mother liquor to different concentration gradients of 1 mg·L –1 , 5 mg·L –1 , 10 mg·L –1 , 30 mg·L –1 , 50 mg·L –1 Then use the ultraviolet spectrophotometer to detect the absorbance of different concentrations of TC at 358 nm, and according to the linear relationship between the absorbance of different concentrations of TC at 358 nm and its concentration value, draw the standard curve for subsequent calculation of TC concentration.

[0029] (3) Fe X -MOFs / CF catalyzes the degradation of tetracycline TC under light conditions: Add 20 mL of TC solution with a concentration of 50 mg·L –1 to a glass bottle, then add 0.004 g of Fe X -MOFs / CF material, and finally add 10 mM H2O2 (30%), with the xenon lamp light source 20 cm away from the glass bottle. Under light conditions, Fe X -MOFs / CF catalyzes H2O2 to generate free radicals to degrade and remove TC, and light can significantly enhance the efficiency of Fe X -MOFs / CF catalyzes H2O2 to generate free radicals. Every hour, 1 mL is taken out at 0 min, 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min, and its absorbance is measured by ultraviolet and the TC concentration of the sample is calculated according to the standard curve, and the degradation efficiency is evaluated according to the ratio of the existing concentration to the initial concentration (C t / C0). The concentration of the sample can also be measured after 60 min of reaction, and the removal rate of TC after 60 min of reaction is calculated.

[0030] (4) The TC degradation efficiency of each time period is represented by C t / C0, and the removal rate is calculated as follows: r = (1– C t / C0) × 100% (5) The composite material Fe XEffect of MOFs / CF on removal of TC in photo-Fenton: Under the condition of ensuring the catalyst dosage, light intensity, H2O2 dosage, TC concentration and other conditions, the catalytic performance of different proportions of composite materials was compared. 0.004 g Fe 0.05 -MOFs / CF, Fe 0.10 -MOFs / CF, Fe 0.15 -MOFs / CF, Fe 0.20 -MOFs / CF, Fe 0.25 -MOFs / CF was added to 20 mL of TC solution with a concentration of 50 mg·L –1 -1. 21.6 μL of H2O2 (10 mM) with a content of 30% was added to the solution, and then it was irradiated under the condition of xenon lamp light source for 60 min. The TC concentration after degradation was tested to calculate the removal rate. The experimental results are shown in Figure 5 -MOFs / CF, Fe 0.05 -MOFs / CF, Fe 0.10 -MOFs / CF, Fe 0.15 -MOFs / CF, Fe 0.20 -MOFs / CF, Fe 0.25 -MOFs / CF, Fe 0.05 -MOFs / CF, Fe 0.15 -MOFs / CF, Fe 0.20 -MOFs / CF, Fe 0.25 -MOFs / CF, Fe 0.20 -MOFs / CF, Fe X -MOFs / CF, Fe

[0031] Example 3: Optimization of Fe 0.20 -MOFs / CF and H2O2 photo-Fenton system in the degradation process under different pH and use conditions, the specific steps are as follows: pH condition optimization: Under the condition of ensuring the H2O2 dosage, TC concentration, catalyst dosage and light intensity, the prepared TC solution was adjusted to pH 2, 4, 6, 8 and 10 by using 0.1 M HCl and 0.1 M NaOH.

[0032] 0.004 g Fe was weighed 0.05 -MOFs / CF, Fe 0.10 -MOFs / CF, Fe 0.15 -MOFs / CF, Fe 0.20 -MOFs / CF, Fe 0.25 -MOFs / CF was added into 20 mL TC solution with a concentration of 50 mg·L –1 , 21.6 μL of H2O2 (10 mM) with a content of 30% was added into the solution, and then the reaction was carried out under the irradiation of a xenon lamp for 60 min. The TC removal rates under different pH conditions are shown in Figure 6 (a). When the pH was 2, 4, 6, 8, and 10, the TC removal rates of the photo-Fenton system were 83.24%, 98.32%, 97.55%, 76.76%, and 69.45%, respectively. Under the condition of peracid, the proton-promoted dissolution may cause partial destruction of the material, and under the condition of alkaline, H2O2 is easy to decompose into O2 and H2O, which reduces the production of free radicals. The pH of 6 is closer to the actual water body, so the pH of 6 is used in the subsequent use.

[0033] Catalyst Fe 0.20 -MOFs / CF dosage optimization: 20 mL TC solution with a concentration of 50 mg·L –1 was added into a 50 mL glass bottle, and then 0.001 g, 0.002 g, 0.003 g, 0.005 g, and 0.005 g Fe 0.20 -MOFs / CF material was added, and finally 21.6 μL of H2O2 (10 mM) was added. Then the glass bottle was placed under the irradiation of a xenon lamp for 60 min to measure the TC concentration. The effects of different Fe 0.20 -MOFs / CF dosages on the TC removal rates are shown in Figure 6 (b). With the increase of the Fe 0.20 -MOFs / CF dosage from 0.05 g·L –1 to 0.25 g·L –1 , the TC removal rate gradually increased. After 60 min of degradation, the Fe –1 -MOFs / CF dosages of 0.05 g·L –1 , 0.10 g·L –1 , 0.15 g·L –1 , 0.20 g·L –1 , and 0.25 g·L 0.20 , the TC removal rates were 86.23%, 92.07%, 93.97%, 96.11%, and 96.25%, respectively.

[0034] The catalyst dosage was 0.20 g·L –1 , 0.25 g·L –1 When the removal rate almost reached a plateau, 0.20 g·L –1 was selected as the optimal dosage from the cost perspective.

[0035] (3) H2O2 concentration optimization: Under the condition of ensuring the Fe 0.20 -MOFs / CF dosage of 0.20 g·L –1 , the TC concentration of 20 mL of 50 mg·L –1 , pH = 6, and the same light conditions, the H2O2 dosage was changed. 10.8 μL, 21.6 μL, 43.2 μL, 64.8 μL, and 86.4 μL of H2O2 were added to the solution, respectively, corresponding to 5 mM, 10 mM, 20 mM, 30 mM, and 40 mM, respectively. Subsequently, the glass bottle was placed under the xenon lamp light source for reaction for 60 min, and then the TC solution concentration after reaction was measured. The results are shown in Figure 6 (c), and the TC removal rates after 50 min of degradation were 88.24%, 95.66%, 97.84%, 98.67%, and 98.99% when the H2O2 usage was 5 mM, 10 mM, 20 mM, 30 mM, and 40 mM, respectively. With the increase of H2O2 concentration, the TC removal rate also increased, and finally reached a plateau. From the economic cost perspective, 30 mM was the final dosage.

[0036] (4) Degradation ability of different TC concentrations by the photo-Fenton system: In order to explore the degradation ability of different concentrations of TC by the photo-Fenton system, the Fe 0.20 -MOFs / CF dosage was 0.20 g·L –1 , the pH was 6, the H2O2 dosage was 30 mM, the TC solution volume was 20 mL, and the light conditions were the same. Different concentration gradients of TC were set to be 10 g·L –1 , 30 g·L –1 , 50 g·L –1 , 70 g·L –1 , and 100 g·L –1 . The TC solution concentration was measured after 60 min of reaction to calculate the removal rate. The results are shown in Figure 6 (d), and the photo-Fenton system had degradation abilities of 10 g·L –1 , 30 g·L –1 , 50 g·L –1 , 70 g·L –1 , and 100 g·L​–1 The removal rates of TC solutions were 97.56%, 98.72%, 98.69%, 96.09%, and 95.32%, respectively. The results showed that the photo-Fenton system had good removal effect on low and high concentration TC solutions.

[0037] Example 4: Explore the removal effect of TC in different systems, mainly investigate whether the single factor variable has an impact on TC degradation and the adsorption performance, Fenton-like performance, photocatalytic performance, and photo-Fenton performance of the material, including the following steps: (1) The degradation effect of H2O2 on TC: 64.8 μL of H2O2 (30 mM) was added to 20 mL of TC solution with a concentration of 50 mg·L –1 -1, and the concentration was measured every 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min to evaluate the degradation efficiency by C t / C0, and the degradation process is shown in Figure 7 (a). The TC removal rate was only 0.57% after 60 min of degradation, and the results are shown in Figure 7 (b). The results show that pure H2O2 (30 mM) can hardly generate free radicals to degrade TC.

[0038] (2) The degradation effect of light on TC: In order to explore the influence of light on the degradation performance, a xenon lamp light source was directly irradiated to 20 mL of TC solution with a concentration of 50 mg·L –1 -1, and the concentration change was checked every 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min to evaluate the degradation efficiency by C t / C0, as shown in Figure 7 (a). The TC removal rate was only 4.24% after 60 min of degradation, and the results are shown in Figure 7 (b). The results show that light can affect the concentration of TC.

[0039] (3) The degradation effect of light + H2O2 on TC: In order to explore the influence of light and H2O2 on the degradation of TC, 64.8 μL of H2O2 (30 mM) was added to 20 mL of TC solution with a concentration of 50 mg·L –1 -1, and the solution was placed under the irradiation of a xenon lamp light source. The concentration was measured every 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min to evaluate the degradation efficiency by C t / C0, and the degradation process is shown in Figure 7(a) shows. The TC removal rate after 60 min of degradation was 12.04%, and the results are shown in Figure 7 (b) shows. The results show that the combination of light + H2O2 has a better TC degradation ability than pure H2O2 and pure light, indicating that light can excite H2O2 to generate a small amount of free radicals for TC degradation.

[0040] (4) Adsorption removal effect of catalyst on TC: In order to evaluate the proportion of the adsorption performance of the catalyst itself in the removal rate of TC in the photo-Fenton system, the adsorption performance of the catalyst was investigated by adding only the catalyst to the TC solution. 0.004 g of catalyst Fe 0.20 -MOFs / CF was added to 20 mL of TC solution with a concentration of 50 mg·L –1 -1, and its concentration change was checked every 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min to evaluate its degradation efficiency by C t / C0, as shown in Figure 7 (a). The TC removal rate after 60 min of degradation was only 8.03%, and the results are shown in Figure 7 (b). The results show that the adsorption ability of the catalyst itself for TC is low.

[0041] (5) Degradation effect of catalyst + light photocatalytic system on TC: In order to evaluate the role of the catalyst + light photocatalytic system in the photo-Fenton, 0.004 g of catalyst Fe 0.20 -MOFs / CF was added to 20 mL of TC solution with a concentration of 50 mg·L –1 -1 and irradiated by a xenon lamp light source, and its concentration change was checked every 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min to evaluate its degradation efficiency by C t / C0, and the degradation process is shown in Figure 7 (a). The TC removal rate after 60 min of degradation was 14.24%, and the results are shown in Figure 7 (b). The results show that the photocatalytic system has a certain degradation effect, indicating that light can excite electron-hole separation for TC degradation, but electron-hole is easy to recombine, and the degradation effect is low, so photocatalysis is not the main role. Photocatalytic reaction formula: Fe 0.20 -MOFs / CF + hν → h + +e - (1) (6) Degradation effect of H2O2 + catalyst Fenton-like system on TC: 0.004 g of catalyst Fe 0.20- MOFs / CF was added to 20 mL of TC solution with a concentration of 50 mg L –1 and 64.8 μL of H2O2 (30 mM) was added, and its concentration change was checked every 10 min, 20 min, 30 min, 40 min, 50 min, 60 min to evaluate its degradation efficiency by C t / C0, and the degradation process is shown in Figure 7 (a). Fe 2+ can activate H2O2 to generate hydroxyl radicals for TC degradation. The reaction is as follows: Fe 2+ + H2O2→ Fe 3+ + ·OH + OH − (2) Fe 3+ + H2O2→ Fe 2+ + ·OOH + H + (3) In the Fenton-like reaction, Fe 2+ reacts with H2O2 to generate Fe 3+ at a very fast rate, but Fe 3+ is reduced to Fe 2+ at a very slow rate, resulting in rapid depletion of Fe 2+ and accumulation of Fe 3+ . The results of the degradation of TC by the H2O2 + catalyst Fenton-like system in this example are shown in Figure 7 (b). After 60 min of degradation, the removal rate of TC was 58.86%, and the results showed that although the Fenton-like system played a leading role in the degradation of TC, there was still room for improvement in the Fe 2+ / Fe 3+ cycle process.

[0042] (7) Degradation of TC by the photo-Fenton system of light + catalyst + H2O2: 0.004 g of catalyst Fe 0.20 -MOFs / CF was added to 20 mL of TC solution with a concentration of 50 mg L –1 and 64.8 μL of H2O2 (30 mM) was added, and the reaction was carried out under the condition of a xenon lamp light source, and its concentration change was checked every 10 min, 20 min, 30 min, 40 min, 50 min, 60 min to evaluate its degradation efficiency by C t / C0, and the degradation process is shown in Figure 6 (a). The reaction of the photo-Fenton system is as follows: Fe 2+ + H2O2→ Fe 3+ + ·OH + OH −(2) Fe 3+ +H2O2 → Fe 2+ +·OOH+H + (3) Fe 0.20 -MOFs / CF+hν → h + +e - (1) Fe 3+ +e - → Fe 2+ (4) In the photo-Fenton reaction, light can stimulate the separation of electrons and holes, and the generated electrons can be 3+ Consumption and thus promotion of Fe in Fenton-like reactions 2+ / Fe 3+ Circulation solution Fe 2+ Rapid consumption of Fe 3+ The problem of accumulation is solved. At the same time, it is difficult for holes to recombine after electrons are consumed, which also enhances the photocatalytic performance. In this embodiment, the degradation effect of the photo-Fenton system of H2O2+catalyst+light on TC is shown in the following figure. ​ (b) After 60 minutes of degradation, the TC removal rate was 99.13%. The results show that the photo-Fenton system can effectively degrade and remove TC. The data of TC degradation process of different reaction systems are shown in the following table:

[0043] The removal rate of TC by different reaction systems in different time periods is r: r=(1-C t / C0)*100%, detailed data is as follows:

[0044] Example 5: Degradation of other organic pollutants by the photo-Fenton system, specific steps: Preparation of 50 mg·L –1 Other organic pollutants include methyl orange MO, methyl blue MB, norfloxacin NFX, enrofloxacin ENR, and oxytetracycline OTC. 0.20 -MOFs / CF was added to 20 mL of a 50 mg·L –1 Methyl orange MO, methyl blue MB, norfloxacin NFX, enrofloxacin ENR, oxytetracycline OTC solution and 64.8 μL of H2O2 (30 mM) were added and reacted under xenon light source. The concentration changes were checked every 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min by C t / C0 to evaluate its degradation efficiency, the degradation process is as follows​ The removal rates of p-methyl orange MO, methyl blue MB, norfloxacin NFX, enrofloxacin ENR and oxytetracycline OTC after 60 min of reaction were 51.28%, 99.41%, 87.84%, 65.33% and 97.31%, respectively. It was shown that the photo-Fenton system had good degradation and removal effects on other organic pollutants. The detailed data of the degradation process changing with time are shown in the following table:

[0045] The removal rates of other organic pollutants by the photo-Fenton system changing with time are shown in the following table:

[0046] The present application uses the green and environmentally friendly photosensitive material 4-carboxyphenyl porphyrin TCPP as an organic ligand, and Fe 2+ The nano Fe-MOFs prepared by taking the green and environmentally friendly photosensitive material 4-carboxyphenyl porphyrin TCPP as an organic ligand and Fe 3+ The nano Fe-MOFs prepared by taking the green and environmentally friendly photosensitive material 4-carboxyphenyl porphyrin TCPP as an organic ligand and Fe

[0047] In addition, the combination technology of nano Fe-MOFs and bio-based cotton fibers in the present application mainly includes plasma cleaning, alkalization treatment and carboxymethyl treatment. Loading the nano Fe-MOFs on the bio-based fiber CF can well avoid the agglomeration of the nano Fe-MOFs and improve the catalytic efficiency. Compared with traditional powder catalytic materials, the three-dimensional composite material Fe 0.20 -MOFs / CF is convenient to recycle after use, and greatly improves the actual use performance of the material. Fe 0.20 The photo-Fenton degradation system of Fe

[0048] It should be noted that although the present patent document is described in the form of separate embodiments, this does not mean that each embodiment only relates to a single technical solution. This way of expression is only for the purpose of clear expression, and the person skilled in the related art should understand the content of the specification from the whole perspective. In fact, the technical solutions disclosed in each embodiment can be reasonably combined according to actual needs, so as to form other technical solutions that can be realized by the person skilled in the art.

[0049] The foregoing embodiment details are merely specific description of feasible implementation of the present application, and are not intended to limit the protection scope of the present application. Any equivalent replacement or modification made based on the core technical concept of the present application shall be considered falling within the protection scope of the present application.

Claims

1. A method for preparing a nano-MOFs-loaded bio-based fiber photo-Fenton catalytic material, characterized in that: The following steps are involved: Step S1, pretreatment of bio-based cotton fiber CF: The cleaned cotton fiber CF was plasma cleaned for 60 seconds, then alkalized to activate the cellulose in the cotton fiber CF, and finally carboxymethylated. This series of measures is conducive to the loading of metal-organic frameworks (MOFs). Step S2, nano-MOFs bio-based fiber composite material Fe X Preparation of MOFs / CF: FeCl2 • 6H2O was dissolved in an organic solvent, and then the cotton fiber CF pretreated in step S1 was immersed in the organic solvent for 8 h; then benzoic acid and 4-carboxyphenylporphyrin TCPP were dissolved therein, and the ratio of benzoic acid: 4-carboxyphenylporphyrin TCPP: FeCl2 • 6H2O was 30:1:5; FeCl2 was hydrothermally reacted at 90 °C for 5 h to obtain Fe X -MOFs / CF; then the prepared Fe X -MOFs / CF was first dried and then washed with ethanol to remove the undissolved ligands to obtain the final nano-MOFs bio-based fiber composite material Fe X -MOFs / CF;Fe X -In MOFs / CF, X represents the doping amount of FeCl2 • 6H2O; In this step, the ratio of benzoic acid: 4-carboxyphenylporphyrin TCPP: FeCl2 • 6H2O = 30:1:5 was kept unchanged, and the volume of the organic solvent was not changed. The loading rate of MOFs on cotton fiber CF was changed by changing the amount of FeCl2 • 6H2O.

2. The method for preparing the nano-MOFs-loaded bio-based fiber photo-Fenton catalytic material according to claim 1, characterized in that: The alkalization treatment in step S1 is to swell the cotton fiber CF and activate the cellulose to facilitate better carboxymethylation. The alkali is a 20% to 30% by mass NaOH solution, 50 ml of NaOH solution corresponds to 0.5 g to 1.0 g of cotton fiber CF, and stirring is performed at room temperature of 25 to 30°C for 1 to 3 hours.

3. The method for preparing the nano-MOFs-loaded bio-based fiber photo-Fenton catalytic material according to claim 1, characterized in that: The carboxymethylation in step S1 is to improve the bonding between MOFs and cotton fiber CF; 50 ml of a 20% to 30% by mass chloroacetic acid solution corresponds to 0.5 g to 1.0 g of cotton fiber CF, and the reaction is carried out at 50° C. to 70° C. for 2 h to 4 h.

4. The method for preparing the nano-MOFs-loaded bio-based fiber photo-Fenton catalytic material according to claim 1, characterized in that: In step S2, the organic solvent is any one of N,N-dimethylformamide and ethanol.

5. The method for preparing the nano-MOFs-loaded bio-based fiber photo-Fenton catalytic material according to claim 1, characterized in that: In step S3, X is 0.05 to 0.

25.

6. The method for preparing the nano-MOFs-loaded bio-based fiber photo-Fenton catalytic material according to claim 5, characterized in that: In the step S3, X is preferably 0.2, that is, benzoic acid, 4-carboxyphenylporphyrin TCPP, and FeCl2 • 6H2O are 1.2 g, 0.04 g, and 0.20 g, respectively, and the nano-MOFs bio-based fiber composite material is Fe 0.2 -MOFs / CF.

7. Use of the nano-MOFs bio-based fiber composite material prepared according to the method according to any one of claims 1 to 6 in photo-Fenton degradation of tetracycline TC and other organic pollutants.

8. The use of the nano-MOFs bio-based fiber composite material for photo-Fenton degradation of tetracycline TC and other organic pollutants according to claim 7, characterized in that: The other organic pollutants include methyl orange MO, methyl blue MB, norfloxacin NFX, enrofloxacin ENR, and oxytetracycline OTC.

9. The use of the nano-MOFs bio-based fiber composite material for photo-Fenton degradation of tetracycline TC and other organic pollutants according to claim 7, characterized in that: The application of light-enhanced composite materials to catalyze hydrogen peroxide H2O2 to produce free radicals for oxidative degradation of tetracycline TC and other organic pollutants. The following steps are involved: Weigh the nano-MOFs bio-based fiber composite material Fe 0.2 -MOFs / CF was added to the treated water containing tetracycline TC and other organic pollutants, and then hydrogen peroxide H2O2 was added to adjust the pH, and a xenon light source was introduced to pass the MOFs bio-based fiber composite material Fe 0.2 -MOFs / CF catalyzes H2O2 to produce free radicals under light conditions to degrade and remove tetracycline TC and other organic pollutants.

10. The use of the nano-MOFs bio-based fiber composite material for photo-Fenton degradation of tetracycline TC and other organic pollutants according to claim 9, characterized in that: The MOFs bio-based fiber composite material Fe 0.2 The dosage of MOFs / CF was 0.05 g·L –1 ~0.25 g·L –1 The amount of hydrogen peroxide H2O2 used is 5 mM ~40 mM; the pH is 2~10; the organic pollutant is 10 mg·L –1 ~100 mg·L –1 ; Xenon lamp light intensity 100 mW / cm².

Citation Information

Patent Citations

  • Iron (III) tetracarboxyl phenyl porphyrin implanted metal organic framework preparation and application

    CN109126877A

  • Cotton fabric with one-way moisture absorption, sweat releasing and antibacterial functions and preparation method thereof

    CN117802771A

  • Bimetal MOFs three-dimensional biomass composite material as well as preparation method and application thereof

    CN119237018A

  • Fibrous porphyrin assembly with polysaccharide used as one-dimensional host

    JP2006248973A